Short Communication: Community of phytoplankton in peatland canal, Riau, and wet dune slacks of Parangtritis, Yogyakarta, Indonesia - Annisa Mawarni; Firda Nabila Nur Azizah; Heni Wahyu Sartika; Suwarno Hadisusanto; Dwinda Mariska Putri; Akbar Reza (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Mawarni A, Azizah FNN, Sartika HW, Hadisusanto S, Putri DM, Reza A. 2020. Short Communication: Community of Phytoplankton in peatland canal, Riau, and wet dune slacks of Parangtritis, Yogyakarta, Indonesia. Biodiversitas 21: 1874-1879. The ecosystems of peatland canal and wet dune slacks have specific characteristics for phytoplankton community. This study aimed to elaborate on the distribution and abundance of phytoplankton community in peatland canal of Sungai Tohor Village, Meranti Islands, Riau and wet dune slacks of Parangtritis, Special Region of Yogyakarta. Phytoplankton was collected using a 2-L modified Van Dorn water sampler. In peatland, canal phytoplankton was sampled at 3 different locations, each with 5 repetitions. Meanwhile, in wet dune slacks, phytoplankton was sampled at 5 locations, each with 3 repetitions. Phytoplankton samples were filtered with Wisconsin plankton-net 120 mesh and fixed with 3 drops of formaldehyde 4%. The measured physical and chemical factors were air temperature, water temperature, dissolved oxygen, alkalinity, carbon dioxide, pH, depth, transparency, nitrate, sulfate, and phosphate concentration. The results showed that the distribution and abundance of phytoplankton community in wet dune slacks were greater than those of the peatland community. This research found 18 species of phytoplankton in peatland canal, dominated by Synedra acus and 116 species of phytoplankton in wet dune slacks, dominated by Cyclotella meneghiniana.